Investigating Branched Polyethylene Sensors for Applications in Prosthetics. Issue 21 (8th October 2021) - Williams, Jamie O. D.; Solan, Gregory A.; Xu, Jinting; Allen, Jack; Harris, Rob C.; Timmermann, Vanessa M.
Abstract: There is a need for new conductive, scalable sensors with piezoresistive and thermoresistive properties for applications in bioengineering. For example, the demand for real‐time sensory feedback in upper‐limb prosthetics requires sensors that are low‐cost, scalable, and sensitive to temperature, pressure, and movement. It is possible to manufacture low‐cost conductive sensors by directly mixing a low‐cost filler such as graphite into fillers such as polyorganosiloxane, although they can have poor electrical and mechanical homogeneity. In this paper, an alternative approach is outlined to form these sensors: ethylene was polymerized using a nickel catalyst to form a polymer with up to 93 branches per 1000 carbon atoms. This branched polyethylene was fibrous and had a greater volume than high‐density polyethylene. After hot pressing with a graphite filler to form a conductive, flexible sensor, the polyethylene samples had electrical resistivity down to ≈ 0.067 Ω m, a thermal coefficient of resistance ≈ −7.5 Ω ∘ C − 1 at 27 ∘ C, and a electrical resistance sensitive to forces down to 0.1 N. The process is scalable, and provides a route to homogeneous, low‐cost sensors for future prosthetics applications. Abstract : There is a need for polymers that have electrical conductivity sensitive to force and temperature stimuli. Scalability and homogeneity is important for future applications in bioengineering, for example, in prosthetics. In this paper, branched polyethylene is synthesized in the laboratory and produced into sensors. The sensitivity of these sensors is then investigated versus alternative high‐density polyethylene examples.